2019
DOI: 10.1515/jbcpp-2019-0014
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of key enzymes linked to Parkinsonism and neurologic disorders by Antiaris africana in rotenone-toxified rats

Abstract: BackgroundThe physiopathologies of many neurologic diseases are characterized by related biochemical dysfunctions that could be explored as drug targets. This study evaluated the effect of a methanol leaf extract of Antiaris africana (MEA) on critical bioindices of Parkinsonism and related neurologic dysfunctions in rats with rotenone-induced neurotoxicity.MethodsAnimals were administered 50 or 100 mg/kg MEA for 14 consecutive days. Rotenone (1.5 mg/kg) was administered three times per day on days 13 and 14. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…These events have been linked with rotenone toxicity. [5,62] Interestingly, our findings showed that DHQ attenuated the rotenone-induced disruption of striatal dopaminergic and cholinergic systems in agreement with previous reports. [2,8,17,20,23] Our findings also revealed that altered glutamate metabolism and mitochondrial complex dysfunction were evident in the striatum of rotenone-toxified rats but controlled by DHQ.…”
Section: Dhq Protects Against Inflammatory Reactions and Modulates Ne...supporting
confidence: 93%
See 3 more Smart Citations
“…These events have been linked with rotenone toxicity. [5,62] Interestingly, our findings showed that DHQ attenuated the rotenone-induced disruption of striatal dopaminergic and cholinergic systems in agreement with previous reports. [2,8,17,20,23] Our findings also revealed that altered glutamate metabolism and mitochondrial complex dysfunction were evident in the striatum of rotenone-toxified rats but controlled by DHQ.…”
Section: Dhq Protects Against Inflammatory Reactions and Modulates Ne...supporting
confidence: 93%
“…[55] The striatal redox imbalance observed in this study is consistent with the pathological features of PD. [5,56] A compromised antioxidant defense system with oxidative stress is reflected in the reduced activities of protective antioxidant factors such as SOD, GPx, CAT, GSH, and FRAP, and the increased XO activity and MDA, nitrate, and PC levels. [2,4] This may be due to insufficiency of the protective antioxidants, increased peroxidation, and/or protein carbonylation coupled with apoptosis.…”
Section: Dhq Protects Against Inflammatory Reactions and Modulates Ne...mentioning
confidence: 99%
See 2 more Smart Citations
“…Extracts of medicinal plants have beneficial effects in experimental models both in vivo ( Rezvani et al, 2010 for V. officinalis , and Ilesanmi et al, 2019 for Antiaris africana ) and in vitro ( Areiza-Mazo et al, 2018 for Physalis peruviana ). Therefore, in addition to the CSD model, we analyzed the V. officinalis /rotenone interaction in a set of in vitro experiments in the rat C6 glioma cell culture model ( Grobben et al, 2002 ; Krylova et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%